Rehabilitation work: supporting desistance and recovery - Graham, Hannah (International series on desistance and rehabilitation, 2016)
Introduction -- Rehabilitation: from paradigms to processes -- Tools and approaches in rehabilitation work -- Navigating the research process -- Alcohol and other drugs rehabilitation work -- Criminal justice and working with offenders -- Allies and adversaries: complexity and the dynamics of collaboration -- Theorising rehabilitation work and the helping professions -- Changing rehabilitation cultures